Electrophysiological mapping of novel prefrontal - cerebellar pathways - Watson, Thomas C.; Jones, Matthew W.; Apps, Richard (Frontiers in Integrative Neuroscience, 2009)
Whilst the cerebellum is predominantly considered a sensorimotor control structure, accumulating evidence suggests that it may also subserve non motor functions during cognition. However, this possibility is not universally accepted, not least because the nature and pattern of links between higher cortical structures and the cerebellum are poorly characterized. We have therefore used in vivo electrophysiological methods in anaesthetized rats to directly investigate connectivity between the medial prefrontal cortex (prelimbic subdivision, PrL) and the cerebellum. Stimulation of deep layers of PrL evoked distinct field potentials in the cerebellar cortex with a mean latency to peak of approximately 35ms. These responses showed a well-defined topography, and were maximal in lobule VII of the contralateral vermis (a known oculomotor centre); they were not attenuated by local anesthesia of the overlying M2 motor cortex, though M2 stimulation did evoke field potentials in lobule VII with a shorter latency. Single-unit recordings showed that prelimbic cortical stimulation elicits complex spikes in lobule VII Purkinje cells, indicating transmission via a previously undescribed cerebro-olivocerebellar pathway. Our results therefore establish a physiological basis for communication between PrL and the cerebellum. The role(s) of this pathway remain to be resolved, but presumably relate to control of eye movements and/or distributed networks associated with integrated prefrontal cortical functions.